Shopee Marketplace Ratings And Reviews - Hilma Farhani; Ratih Ayu Sekarini; Bambang Sukamto (International Journal of Management Research and Economics, 2023)
The aim of this research is to determine how reviews and ratings on the Shopee marketplace affect consumer buying interests. The population of this study is the consumer marketplace Shopee in Jakarta. Purposive sampling is used in conjunction with a non-probability sampling strategy. A sample of 85 respondents who made purchases on the Shopee marketplace the purpose of the data analysis process used in this study is to evaluate the hypothesis. PLS (partial least squares) software was used in this study. According to research findings, reviews have a greater impact on buying decisions than rankings. Buy interest is influenced by reviews and ratings of 59%.